2019
DOI: 10.1002/slct.201803300
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solar Conversion of CO2 to CO Using Mn‐doped TiO2 Based on Photo‐thermochemical Cycle

Abstract: Photo-thermochemical cycle (PTC) is a promising method to converting CO 2 to solar fuels. To study the mechanism of CO 2 reduction based on PTC, sol-gel synthesized titanium dioxide (ST) and Mn-doped TiO 2 (MT) films were produced and applied to the PTC under simulated solar light irradiation. Commercial P25 (PT) was used as a reference. Experiments show that Mndoped TiO 2 produced more CO than undoped TiO 2 and P25. The average CO production of 1.0 wt% MT by the PTC was 32.19 μmol⋅m À 2 ⋅h À 1 ), 4.36 times t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The oxygen vacancy generation was attributed to the high oxygen atom density and low Bi–O bond energy in {001} facets. Moreover, it is widely accepted that at ambient conditions UV–vis photons can produce oxygen vacancies on the metal oxide surface in the first step of the photothermochemical cycle. The following reaction occurs on the metal oxide (M x O y ) surface when it is exposed to light irradiation Thus, the generation of oxygen vacancies in CeO 2 -SAC can be explained as follows.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen vacancy generation was attributed to the high oxygen atom density and low Bi–O bond energy in {001} facets. Moreover, it is widely accepted that at ambient conditions UV–vis photons can produce oxygen vacancies on the metal oxide surface in the first step of the photothermochemical cycle. The following reaction occurs on the metal oxide (M x O y ) surface when it is exposed to light irradiation Thus, the generation of oxygen vacancies in CeO 2 -SAC can be explained as follows.…”
Section: Resultsmentioning
confidence: 99%
“…The photo and photothermal CO 2 reduction activity of TiO 2 with abundant V O s was significantly improved because of the enhanced charge separation and visible light absorption . Zhang et al utilized TiO 2 doped with transition metals (Mn, Ni, Cu, and Zn) and loaded it with Pd nanoparticles for the photothermal CO 2 RR to produce CO and verified that the surface V O s increased the catalytic activity. ,, In addition, surface modification with metals or metal oxides is a common method for increasing CO 2 RR activity and product selectivity. , Recently, Au-loaded TiO 2 has been widely studied and was found to efficiently improve the photocatalytic CO 2 reduction performance and promote high CH 4 selectivity, which resulted from enhanced visible light absorption owing to Au surface plasmon resonance, as well as increased charge separation because of electron transfer between Au and TiO 2 . The V O s on TiO 2 can effectively stabilize Au single atomic sites, which also promote the catalytic properties. , Theoretical calculations of Au loading on the surface of TiO 2 have also been conducted. Furthermore, many researchers have reported that doping of the alkaline metal oxide MgO on TiO 2 played a critical role in CO 2 methanation because of its strong chemisorption of CO 2 , which initiated the CO 2 RR. …”
Section: Introductionmentioning
confidence: 99%
“…24 Zhang et al utilized TiO 2 doped with transition metals (Mn, Ni, Cu, and Zn) and loaded it with Pd nanoparticles for the photothermal CO 2 RR to produce CO and verified that the surface V O s increased the catalytic activity. 11,12,25 In addition, surface modification with metals or metal oxides is a common method for increasing CO 2 RR activity and product selectivity. 26,27 Recently, Au-loaded TiO 2 has been widely studied and was found to efficiently improve the photocatalytic CO 2 reduction performance and promote high CH 4 selectivity, which resulted from enhanced visible light absorption owing to Au surface plasmon resonance, as well as increased charge separation because of electron transfer between Au and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work of Fujishima and Honda in 1972, TiO 2 has been investigated extensively in mechanistic studies on the H 2 O splitting reaction. , Doping TiO 2 with transition metals (such as Mn, Fe, Co, Ni, Cu, and Zn) could promote surface V O formation. ,,, Additionally, V O self-healing on during H 2 O splitting has been demonstrated . On anatase TiO 2 , the surface-bridging peroxo dimer (O 2 2– ) is a stable intermediate, composed of one H 2 O and one surface lattice oxygen atom, and molecular O 2 evolves directly from O 2 2– . , On rutile TiO 2 , the bridging oxygen radical (O br – ) promotes the removal of lattice oxygen .…”
Section: Introductionmentioning
confidence: 99%